Malignant stromal tumor of the duodenum - Misa, Ricardo; Arévalo, Carlitos; Ferrés, Martín; González, Rosana; Tchekmedyian, Vartan; Vilas, Ana; Rodríguez, Julio (Cirugía del Uruguay, 2005)
A patient presented a clinical case of stromal tumor of duodenum. Thes9. tumors have low incidence so we proceeded to a, ,.1/yze the pathology of stromal tumors of the digestive tract in search of prognostic e/ements indicating malignancy. Treatment shou/d, in the first place be surgical in arder to permit resection with adequate margins. Discussion includes the use of tyrosine kinase inhibitors as adjuvant therapy to be indicated in specific circumstances.